2020
DOI: 10.1111/1759-7714.13649
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor resection of non‐small cell lung cancer patients with ipsilateral pleural dissemination (M1a) in the era of targeted therapy

Abstract: Background Non‐small cell lung cancer (NSCLC) patients with ipsilateral pleural dissemination (M1a) are generally contraindicated for surgery. Recently, several studies have demonstrated that these patients might benefit from primary tumor resection (PTR). However, whether PTR is beneficial for driver oncogene‐positive patients treated with targeted therapy, remains unclear. Here, we investigated the effects of PTR on survival in the era of targeted therapy. Methods In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…In subgroup analysis, we found that patients could not get survival benefit from tumor resection if they received targeted therapy, while tumor resection could improve OS in the patients who received chemotherapy alone. The results was in accordance with the recent study that reported by Li et al [ 24 ]. These indicated that tumor resection may be only beneficial for a subgroup of patients with UPD who did not have the driver gene mutation or could not receive targeted therapy due to cost, allergy, adverse events or other factors.…”
Section: Discussionsupporting
confidence: 94%
“…In subgroup analysis, we found that patients could not get survival benefit from tumor resection if they received targeted therapy, while tumor resection could improve OS in the patients who received chemotherapy alone. The results was in accordance with the recent study that reported by Li et al [ 24 ]. These indicated that tumor resection may be only beneficial for a subgroup of patients with UPD who did not have the driver gene mutation or could not receive targeted therapy due to cost, allergy, adverse events or other factors.…”
Section: Discussionsupporting
confidence: 94%
“…In view of the lack of significant early symptoms of lung cancer, patients are often in an advanced stage [ 6 ]. In recent years, the targeted therapy of lung cancer has made important progress, and a variety of targeted drugs emerge in endlessly [ 7 , 8 ]. In order to further improve the prognosis of patients, it is still necessary to identify more potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the non-targeted therapy group, PTR significantly prolonged survival (MST: 39.8 vs. 14.2 months, P=0.002) (37). This single-center retrospective study suggested PTR conferred a better outcome in M1a patients who were not candidates for targeted therapy.…”
Section: Surgery For Patients With Different Genetic Mutationsmentioning
confidence: 70%
“…(I) For cM0 but pathological staging pM1a patients, which means "unexpected" pleural dissemination during surgery, surgeons should try to resect the main tumor to prolong patients' survival and harvest enough tissue for gene testing. (II) For clinical staging pM1a patients, such as MPE confirmed by cytopathology, surgical intervention should be carefully included as an important option of multimodal therapy regimens, especially for patients with negative driver mutations and lymph node-negative (37). (III) The surgery would only be considered in operable patients, and should be relatively contraindicated for patients with N2/N3 metastasis or malignant pericardial effusion because of the poor survival after PTR (33) make patients receive systemic therapy sooner, thoracic surgeons should consider the VATS technique superior to thoracotomy.…”
Section: Hithoc For M1a Nsclc Patientsmentioning
confidence: 99%